O teatro em espaços altenativos: um estudo etnográfico sobre dois grupos de teatro de Santa Maria RS - Weisheimer, Susan Deisi (2013)
This work consists of ethnographic study on two theater groups of Santa Maria RS, the group EMAET and the TeatroVagaMundo. These groups have distinct features: the former is a theater school for people who are not actors/actresses and the latter constitutes itself as a professional/independent theater group. However both also carry out their works beyond the theater building, conventional space of the theater. It is mainly due to this characteristic that these groups were chosen for this study. Therefore the objective of this work is to understand the theatrical productions of these groups through participant observation in their quotidian of classes and/or rehearsals and performances, as cultural performances based on the theoretical scope of the performance studies at theater and anthropology and in discussions about street, street theater and alternative space categories.